The Influence of Social Media Content on Students' Learning Interest in the Digital Era - Mohammad Arridho Nur Amin (Gestion Educativa, 2025)
The development of digital technology has changed the way students access information and influenced their learning interests in the modern era. This study uses a Literature Review method to analyze the influence of social media content on students' learning interests. The literature reviewed includes national and international journals, scientific proceedings, and academic books relevant to the topic, with a focus on educational, entertainment, and interactive content. The results of the study indicate that students utilize platforms such as Instagram, TikTok, YouTube, and X intensively to obtain academic information. Creative and interactive educational content increases motivation and learning engagement, while excessive entertainment content can be distracting. Digital literacy is an important factor for students to assess the credibility and relevance of content. Digital interactions through comments, information sharing, and group discussions support collaborative learning and a more in-depth learning experience. The integration of social media into learning strategies allows for a more adaptive curriculum, increases engagement, and strengthens information retention. This study emphasizes the need for structured and evidence-based use of social media to support the effectiveness of students' learning processes. These findings form the basis for developing innovative digital learning strategies that are responsive to the needs of today's generation of students.